The impact of digital transformation on E-recruitment performance: An empirical study - Elmenzhi, Zenab; Fassi, Samia El; Frij, Rafia; Lhassan, Imad Ait; Maghni, Ahmed (Edelweiss Applied Science and Technology, 2025)
This study investigates the impact of digital transformation on the performance of e-recruitment in companies based in the northern region of Morocco. The purpose of the research is to understand how factors such as digital maturity, stakeholder influence, and data analytics contribute to the effectiveness of digital recruitment processes. A quantitative research design was employed, involving the distribution of a structured questionnaire to 117 companies, and data were analyzed using structural equation modeling (SEM) to test the proposed conceptual model and hypotheses. The findings reveal that digital transformation significantly enhances e-recruitment performance, with digital maturity and the use of social media emerging as key drivers. The study concludes that digital tools and competencies are essential for optimizing recruitment outcomes in a digital context. In terms of practical implications, the results offer valuable insights for HR managers and decision-makers aiming to improve recruitment efficiency through digital strategies, highlighting the need to invest in digital capabilities and stakeholder engagement to remain competitive in talent acquisition.